The Strength of the Wolf is the Pack: U-boat Tactics in the Battle of the Atlantic - Lloyd, Peter G.; MacKay, Niall J.; Price, Christopher (The Northern Mariner / Le marin du nord)

(untitled) (Canadian Nautical Research Society and North American Society for Oceanic History, 2025)
In winter 1942–43 unique circumstances gave Germany’s U-boats the possibility of temporary victory in the North Atlantic. At the same time, Royal Navy operational research considered the possible German adoption of developed stand-off salvo tactics (“browning”), better suited to attacking large, dense convoys than Germany’s existing “ace” tactics of individual commanders infiltrating convoys. We test and verify the RN studies with a simulation, confirming that such tactics would have greatly increased U-boat success. While not denying ultimate Allied victory, “browning” would have increased sinkings, threatened the viability of large convoys, and possibly averted the May 1943 rout, at a critical juncture for Allied strategic decision-making. German lack of OR, Nazi heroic culture, and Dönitz’s methods all contributed to the absence of the feared tactical evolution.